Tonsillar synovial sarcoma, unusual anatomical location: case report and literature review - Sohaib M. Al-Khatib; Maram M. AlSheyab; Sura B. AlOmari (BMC, 2024)
Abstract Background Synovial sarcoma is a rare soft tissue malignancy, occasionally found in the head and neck region. The diagnosis necessitates a multidisciplinary approach involving the clinical presentation, proper imaging studies and histological confirmation, with molecular testing for definitive identification. Treatment entails surgical resection with adjuvant therapies as needed. Case presentation A 33-year-old male patient presented with globus sensation concomitant with right-sided neck swelling. He was clinically found to have right tonsil enlargement with posterior extension. Therefore, he underwent right tonsillectomy with pharyngoplasty. Histopathological examination revealed a biphasic tumor consistent with synovial sarcoma, confirmed by immunohistochemistry and fluorescence in situ hybridization. Conclusions Tonsillar synovial sarcoma represents a diagnostic challenge, requiring a high index of suspicion and comprehensive evaluation. With only twenty previously published cases documented in the literature, awareness of this rare presentation is crucial for prompt diagnosis and appropriate management. Collaboration among multidisciplinary healthcare teams and ongoing research efforts are essential for optimizing diagnostic accuracy, treatment efficacy, and patient outcomes in this rare malignancy.